BLNK suppresses pre–B-cell leukemogenesis through inhibition of JAK3 - Nakayama, Joji (American Society of Hematology, 2009)
Pre–B-cell leukemia spontaneously develops in BLNK-deficient mice, and pre–B-cell acute lymphoblastic leukemia cells in children often lack BLNK protein expression, demonstrating that BLNK functions as a tumor suppressor. However, the mechanism by which BLNK suppresses pre–B-cell leukemia, as well as the identification of other genetic alterations that collaborate with BLNK deficiency to cause leukemogenesis, are still unknown. Here, we demonstrate that the JAK3/STAT5 signaling pathway is constitutively activated in pre-B leukemia cells derived from BLNK(−/−) mice, mostly due to autocrine production of IL-7. Inhibition of IL-7R signaling or JAK3/STAT5 activity resulted in the induction of p27(kip1) expression and cell-cycle arrest, accompanied by apoptosis in the leukemia cells. Transgene-derived constitutively active STAT5 (STAT5b-CA) strongly synergized with the loss of BLNK to initiate leukemia in vivo. In the leukemia cells, exogenously expressed BLNK inhibited autocrine JAK3/STAT5 signaling, resulting in p27(kip1) induction, cell-cycle arrest, and apoptosis. BLNK-inhibition of JAK3 was dependent on the binding of BLNK to JAK3. These data indicate that BLNK normally regulates IL-7–dependent proliferation and survival of pre–B cells through direct inhibition of JAK3. Thus, somatic loss of BLNK and concomitant mutations leading to constitutive activation of Jak/STAT5 pathway result in the generation of pre–B-cell leukemia.